Claims in the administrative contentious process - Salas Ferro, Percy (2012)
The claim is one of the central institutions of the contentious administrative process since it affects its commencement, development and culmination. In this article, the author addresses the fundamental aspects, from a theoretical and practical perspective, of each of the claims proposed in an administrative contentious proceeding such as the claim for annulment or nullity, the claim for the acknowledgement or reestablishment of the law, the claim for a statement contrary to law and the cessation of a material act, the claim for fulfillment and the claim for compensation. A few practical cases are included at the end of this paper aimed at contributing to the suitable formulation and evaluation of each one of the referred claims or petitions.